Petrology, structure and exhumation of the southern Sawatch mountains, south-central Colorado - Robbins, Rebecca (Kansas State University, 2005)
The southern Sawatch Range of the Southern Rocky Mountains of south-central Colorado is composed of Precambrian crystalline igneous and metamorphic rocks that have undergone at least three major mountain building events during the Phanerozoic, the Ancestral Rockies Orogeny, the Laramide Orogeny, and Rio Grande rifting. In order to determine how the ancient basement structures might have influenced later episodes of deformation, a small area of basement terrain was mapped along the western margin of the Poncha Pass transfer zone between the San Luis and Upper Arkansas basins in the northern Rio Grande rift. The two dominant rock types in the map area, (hornblendic) amphibolite gneiss and (felsic) quartzofeldspathic gneiss, may represent interlayered metabasalt/metadiorite and metarhyolite/metagranite, with lenses of exotic lithologies throughout. Metamorphic foliations were found to be oriented predominantly N35ºW 47ºNE and to have had an influence on younger brittle structures related to the rifting episode. Lineations and fractures in the gneissic fabric also are parallel to brittle deformation structures. Apatite Fission-Track (AFT) analysis provided a means of determining when this crust was exhumed and cooled by the removal of overburden in response to erosion and/or tectonics. The resultant AFT age distribution revealed that exhumation occurred at the higher elevations during the Laramide orogeny (~299-46 Ma), and at lower elevations during Rio Grande rifting (~29-19 Ma). Although it is commonly thought that these mountains were exhumed during the rifting episode, the results of this study indicate that older events played a significant role in the exhumation.
Keywords: Precambrian paleoproterozoic; Southern Sawatch range; Felsic hornblendic gneiss; Exhumation; Apatite fission-track; Thermochronology; Geology (0372)